2014
DOI: 10.2508/chikusan.85.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for body weight and ten body measurements at different age stages in Breton and Percheron horses

Abstract: We estimated the genetic parameters for body weight and ten measurements (height at withers, height at croup, body length, chest depth, chest width, hip width, croup width, rump length, chest girth, and cannon bone circumference) at different ages in Breton and Percheron horses. Data included 307 Breton and 324 Percheron horses born between 1999 and 2011 at the Tokachi Station, National Livestock Breeding Center, Japan. The animals were measured every two months on average. Three age groups (birth to 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Maternal effects on early growth have been reported in animals such as beef cattle and sheep (Meyer, 1992; Safari et al, 2005). The existence of maternal effect, mainly derived from dam milk in addition to direct genetic effects (Hintz et al, 1978) and environmental factors (Yamamoto et al, 1993), has also been suggested in horses (Masuda et al, 2014; Yamamoto et al, 1993); however, no reports have estimated this effect. The HKD tested in this study were managed on the farm in the same way for 28 years, and foals were reared with dams after birth without supplementary feeding until weaning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal effects on early growth have been reported in animals such as beef cattle and sheep (Meyer, 1992; Safari et al, 2005). The existence of maternal effect, mainly derived from dam milk in addition to direct genetic effects (Hintz et al, 1978) and environmental factors (Yamamoto et al, 1993), has also been suggested in horses (Masuda et al, 2014; Yamamoto et al, 1993); however, no reports have estimated this effect. The HKD tested in this study were managed on the farm in the same way for 28 years, and foals were reared with dams after birth without supplementary feeding until weaning.…”
Section: Resultsmentioning
confidence: 99%
“…As foals are usually reared with their dams until weaning, maternal effects associated with dam lactation may influence foal growth during this period. Therefore, maternal effects should also be considered with direct genetic effects when analyzing data on foal growth (Masuda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation